2013
DOI: 10.3892/mco.2013.165
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aquaporin-1 is a poor prognostic factor for stage II and III colon cancer

Abstract: Abstract. Colorectal cancer is a major cause of cancer-related mortality worldwide, with a high incidence of recurrence following curative resection, particularly among patients with stage II and III disease. There is therefore a need for novel prognostic biomarkers for advanced colon cancer and it was recently reported that aquaporin-1 (AQP1) may be associated with aggressive characteristics of colon cancer cells in experimental data. The association of clinicopathological findings with AQP1 expression was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 18 publications
3
53
0
Order By: Relevance
“…Although the precise mechanism for AQP1-enhanced motility remains unknown, both ion and water channels are essential in the cellular migration process (Schwab et al, 2007). AQP1 expression has been linked to metastasis and invasiveness of colon cancer cells (Jiang, 2009;Yoshida et al, 2013). In mammary and melanoma cancer cells, AQP1 facilitates tumor cell migration in vitro and metastasis in vivo (Hu and Verkman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanism for AQP1-enhanced motility remains unknown, both ion and water channels are essential in the cellular migration process (Schwab et al, 2007). AQP1 expression has been linked to metastasis and invasiveness of colon cancer cells (Jiang, 2009;Yoshida et al, 2013). In mammary and melanoma cancer cells, AQP1 facilitates tumor cell migration in vitro and metastasis in vivo (Hu and Verkman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various studies have focused on the association of AQPs with carcinoma and reported that several types of cancer express AQP-1, which may be involved in carcinogenesis and tumor progression [14]- [19]. These observations suggested a potential role of AQP-1 in BTC.…”
Section: Discussionmentioning
confidence: 99%
“…High AQP1 expression has been shown as an independent predictive value for poor outcome. 16,17,24 Aquaporin 1-expressing tumor cells were also showed increased plasma membrane osmotic water permeability and accelerated migration. 13 In our series of 62 hilCC, proportional hazard regression analysis (Table 2) showed that AQP1 expression was an independent significant predictor of survival (P < .01).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results from AQP1-null mice also greatly showed reduced tumor growth and improved survival (compared with wild-type mice) when implanted subcutaneously with tumor cells, 9 and in vitro studies indicated the same results. 16,17,24 A possible reason is that AQP1 in tumor cells allow water to rapidly penetrate into the growing tumor mass and tumor AQP1 expression may thus cause tumor expansion by exacerbating tumor-associated edema that might be correlated with poor prognosis. In this clinical survey on AQP1 expression in vitro, we found strong AQP1 expression is an independent indicator for an adverse prognosis in hilCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation